EXERCICE : (2 + 1 + 1,5 + 1,5 = 6 pts)

On considère l’expression E = (2x + 5)2 – (2x + 5)(x – 3).
1. Développer et réduire E.
2. Calculer E pour x = 2 puis pour x = 3 .
3. Factoriser E.
4. Résoudre l’équation (2x + 5)(x + 8) = 0.

Merci d'avance

1

Réponses

2014-05-29T21:03:17+02:00
On considère l’expression E = (2x + 5)2 – (2x + 5)(x – 3). 
1. Développer et réduire E.

E = 4x² + 20x +25 - (2x² - 6x +5x -15)
E = 4x² +20x +25 - 2x² +6x -5x +15
e = 2x² +21x + 40

2. Calculer E pour x = 2
E = 8 + 42 +40 = 90

puis pour x = 3 .
E = 18 + 63 + 40 = 121

3. Factoriser E.
e = (2x+5)(2x +5 - x +3)
E = (2x+5)( x +8)

4. Résoudre l’équation (2x + 5)(x + 8) = 0.

soit 2x +5 = 0
2x = -5
x = -5/2

soit x +8 = 0
x = -8